Lili - Hartanto, Jessika Nadia (Nanyang Technological University, 2023)
“Lili” is a 2D animated film about losing a loved one and processing grief with loved ones around you. The film follows the perspective of Tama, the short-haired girl who recluses herself after losing one of her dear friends, Lili, in a motorcycle accident. She recluses herself from her other friend, Cindy, who was also involved in the accident. This FYP report discusses the process and development of this animated film.